التعزير للمصلحة وأثره في حفظ النظام العام دراسة تأصيلية تطبيقية في المحاكم السعودية (مجلة كلية العلوم الاسلامية, 2022)
يعالج هذا البحث مسألة التعزير للمصلحة وأثره في حفظ النظام العام مع ذكر نموذج للتطبيق القضائي في المملكة العربية السعودية مع الإشارة إلى أحد الأنظمة المرتبطة بالتعزيز. ومنهج البحث هو تحليلي وتطبيقي.ويهدف البحث:إلى ربط مسائل الفقه بالمصلحة الشرعية المعتبرة والبحث عن وربط الجوانب النظرية بالجوانب التطبيقية القضائية وكذلك ربط التعزير بالنظام العام .ومن نتائج البحث: الترابط الوثيق بين التعزير والمحافظة على النظام العام. أهمية النظام العام في حياة الناس. الارتباط الوثيق بين الجوانب النظرية والتطبيقية وهو ما عنيت بدراسته في بحثي من خلال التطبيقات القضائية.  ومن التوصيات :أنه تحتاج  باقي  الأنظمة  إلى كثير من الدراسة في تطبيق هذه المسألة عليها. إعداد البحوث العلمية التي تخدم المستجدات ومن ذلك عقوبة التعزير والتي تستجد يومًا بعد يوم. . وربط الجوانب التطبيقية بالنظرية وربط التعزير بالنظام العام . This research deals with the issue of the Discretionary Punishment (Al-Ta'zir) for the Interest and its Effect in Keeping the Public Regulation, with a model for judicial application in the Kingdom of Saudi Arabia, with reference to one of the regulations related to the discretionary punishment. The research used the analytical and applied approach.The research aims to link the issues of jurisprudence with the legitimate interest, and to search for and link the theoretical aspects with the applied judicial aspects, as well as linking the discretionary punishment to the public regulation. The findings of the research as follows: The close relationship between the discretionary punishment and keeping the public regulation. The importance of public regulation in people's life. The close relationship between the theoretical and practical aspects, which is what I intended to study in my research through judicial applications. The recommendations as follows: The rest of the regulations need a lot of study in applying this issue to them. Doing scientific research that serves developments, including the discretionary punishment, which is emerging day after day, and linking the applied aspects to theoretical aspects and linking the discretionary punishment to the public regulation.